c-C 5 H 5 on a Ni(1 1 1) surface: Theoretical study of the adsorption, electronic structure and bonding - German, Estefania (2008)
In the present work the ASED-MO method is applied to study the adsorption of cyclopentadienyl anion on a Ni(1 1 1) surface. The adsorption with the centre of the aromatic ring placed above the hollow position has been identified to be energetically the most favourable. The aromatic ring remains almost flat, the H atoms are tilted 17° away from the metal surface. We modelled the metal surface by a two-dimensional slab of finite thickness, with an overlayer of c-C 5 H 5 - , one c-C 5 H 5 - per nine surface Ni atoms. The c-C 5 H 5 - molecule is attached to the surface with its five C atoms bonding mainly with three Ni atoms. The Nisingle bondNi bond in the underlying surface and the Csingle bondC bonds of c-C 5 H 5 - are weakened upon adsorption. We found that the band of Ni 5 d z 2 orbitals plays an important role in the bonding between c-C 5 H 5 - and the surface, as do the Ni 6s and 6p z bands.